1998
DOI: 10.1016/s0014-5793(98)01087-4
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of D‐aspartic acid by the rat testis and its role in endocrinology of the testis and spermatogenesis

Abstract: The D-isomer of aspartic acid (D-Asp) has been found in rat testes. In the present study, samples of testicular venous blood plasma, rete testis fluid, interstitial extracellular fluid, luminal fluid from the seminiferous tubules, testicular parenchymal cells, epididymal spermatozoa and peripheral blood plasma were collected and analyzed for D-Asp by two methods, an enzymatic and a chromatographic HPLC method. The two methods gave very similar results for all samples. The highest concentrations of D-Asp (about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Intraperitoneal administration of -Asp to adult male rats induces -Asp accumulation in the pituitary gland and testis, followed by a significant increase in luteinizing hormone, testosterone, progesterone (D'Aniello et al 2000a) and prolactin (D'Aniello et al 2000b) in the blood. Moreover, -Asp is contained in spermatids (Sakai et al 1998b) and both Leydig (D'Aniello et al 1998b, Nagata et al 1999a and Sertoli cells (D'Aniello et al 1998b), and in vitro experiments performed on isolated testis demonstrated that this amino acid enhances the production of testosterone (D'Aniello et al 1996). These data indicate that -Asp may act as a novel putative regulator of hormonal synthesis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intraperitoneal administration of -Asp to adult male rats induces -Asp accumulation in the pituitary gland and testis, followed by a significant increase in luteinizing hormone, testosterone, progesterone (D'Aniello et al 2000a) and prolactin (D'Aniello et al 2000b) in the blood. Moreover, -Asp is contained in spermatids (Sakai et al 1998b) and both Leydig (D'Aniello et al 1998b, Nagata et al 1999a and Sertoli cells (D'Aniello et al 1998b), and in vitro experiments performed on isolated testis demonstrated that this amino acid enhances the production of testosterone (D'Aniello et al 1996). These data indicate that -Asp may act as a novel putative regulator of hormonal synthesis.…”
Section: Introductionmentioning
confidence: 96%
“…Maximal content and transient emergence of -Asp in these tissues correspond to their morphological and functional maturation (Hashimoto et al 1993. In the adenohypophysis, pineal gland and testis in particular, -Asp is involved in hormone synthesis and release (Dunlop et al 1986, Fisher et al 1991, Hashimoto et al 1993, Hashimoto & Oka 1997, D'Aniello et al 1998b, 2000a,b, Ishio et al 1998, Takigawa et al 1998, Wang et al 2002. The relationship between -Asp and endocrine activity has been well documented.…”
Section: Introductionmentioning
confidence: 98%
“…1). The rat epididymides and epididymal fluid contain very low levels of D-Asp compared to the testis, 36,37) suggesting that elongate spermatids leave most of their D-Asp in the seminiferous tubules when cells expel cytoplasm in the tubules during migration into the epididymides and maturation to free spermatozoa. Therefore, DAsp appears to function in the testis rather than spermatozoa.…”
Section: Adrenal Glandmentioning
confidence: 99%
“…First, very high amounts of D-Asp are detected in the tubules, and levels in the rat testicular venous blood plasma are higher than in peripheral blood plasma. 37) Second, intraperitoneally administered D-Asp accumulates outside the tubule rather than being incorporated inside, suggesting that the amino acid is not transported. Thus, we conclude that DAsp is newly synthesized within the tubules.…”
Section: Adrenal Glandmentioning
confidence: 99%
“…reptiles [14], amphibians [15 -17], and in the following rat endocrine glands: pineal [18] [19], pituitary [9] [10] [20 -23], adrenal [24], and testes [9] [15] [20] [21] [25], and in boar testes [26]. It rat, it has been observed that d-Asp is able to elicit the release and synthesis of gonadotropin releasing hormone (GnRH) from the hypothalamus, luteinizing hormone (LH), growth hormone (GH), and prolactin (PRL) from the pituitary gland [22] [27], melatonin synthesis from rat pinealocytes [28], GABA and dopamine [29], and testosterone from rat Leydig cells [30] [31].…”
mentioning
confidence: 99%